Skeletal Muscle Mass Index Predicts Postoperative Complications in Intestinal Surgery for Crohn's Disease. Issue 4 (23rd August 2019) - Galata, Christian; Hodapp, Janina; Weiß, Christel; Karampinis, Ioannis; Vassilev, Georgi; Reißfelder, Christoph; Otto, Mirko
Abstract: Background: The aim of this study was to evaluate the role of the skeletal muscle mass index (SMI) for major postoperative morbidity in patients with Crohn's disease (CD) and intestinal surgery at a tertiary referral center. Methods: A retrospective analysis of the prospectively maintained database for surgical patients with CD at our institution was performed. The cases of all patients operated on between December 2009 and December 2017 with sectional imaging prior to surgery were eligible for this study. Results: A total of 230 patients were included. Major postoperative complications were observed in 32 patients (13.9%). Common intestinal procedures were ileocecal resections (51.7%), segmental small‐bowel resections (10%), and colectomy or proctocolectomy (8.3%). In multivariable analysis, SMI ( P  = .002; odds ratio = 0.914) was the only independent risk factor for major postoperative complications. Both computed tomography (CT) and magnetic resonance imaging (MRI) studies were suitable to determine SMI. The cutoff values for SMI were 31.8 cm 2 /m 2 for females and 41.5 cm 2 /m 2 for males. Conclusion: We present the largest published cohort investigating SMI with regard to major postoperative morbidity in surgery for CD. In multivariable analysis, SMI was the only significant risk factor for Clavien‐Dindo complications grade ≥III. Lumbar SMI was reliably determined by CT and MRI alike. Because preoperative abdominal imaging with either modality is common for patients with CD, SMI could be a reliable and largely available tool to stratify the risk of postoperative complications.